2021
DOI: 10.1111/iar.12426
|View full text |Cite
|
Sign up to set email alerts
|

A major change in magma sources in late Mesozoic active margin of the circum‐Sea of Japan domain: Geochemical constraints from late Paleozoic to Paleogene mafic dykes in the Sergeevka belt, southern Primorye, Russia

Abstract: More than 30 mafic dykes crop out in the Sergeevka belt in the coastal South Primorye, Far East Russia, of which geologic settings have been unclear for years. This study conducted major-and trace elements characterization, Sr-Nd isotope analyses, and Ar-Ar amphibole and U-Pb zircon datings for these rocks in order to identify their origin. The results demonstrated that all dykes are characterized by high Ba/Yb and low Nb/Y, Zr/Y, and Th/Yb ratios, which suggest their origin from arc melts derived from thin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 84 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Some plume-related complexes of East Russia, Japan, Northeast China, and Mongolia [8][9][10][11]20] also formed a part of this suite. The more recent tectonic and petrological studies [21][22][23] strongly confirmed this suggestion. The East-Asian Adakitic Province in Figure 2 shows a surficial projection of the plume-flat subduction interaction that provided the anomalous endogenous and metallogenic activities in the region during CTGE.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Some plume-related complexes of East Russia, Japan, Northeast China, and Mongolia [8][9][10][11]20] also formed a part of this suite. The more recent tectonic and petrological studies [21][22][23] strongly confirmed this suggestion. The East-Asian Adakitic Province in Figure 2 shows a surficial projection of the plume-flat subduction interaction that provided the anomalous endogenous and metallogenic activities in the region during CTGE.…”
mentioning
confidence: 62%
“…The detailed mineralogical, isotopic (Nd, Sr, C, O) and geochemical petrological studies [8,10,23,[25][26][27][28][29][30] clearly identified a deep enriched mantle source of the meimechitepicrite rocks (Figure 6) that is close to the source of the kimberlitic melts. The kimberlitic affinity is especially well manifested by the mineral suite including diamond, picroilmenite, and Ti-rich Cr-spinel (Figure 7).…”
Section: Mafic-ultramafic Related Deposits Ariadny Metallogenic Belt ...mentioning
confidence: 99%
See 3 more Smart Citations